Bibliometric Analysis of Lead's Effects on the Nervous System - Sekartaji, Hapsari Lintang; Hartoyo, Edi; Febriana, Silvia Kristanti Tri; Noor, Zairin; Sanyoto, Didik Dwi; Iskandar, Iskandar (Berkala Kedokteran, 2024)
Lead (Pb) is a heavy metal that is proven to cause various health problems. In its development, research trends on the effects of Pb on the nervous system are still a topic of research. This study aims to identify trends, research focus, and research contributions to understanding the impact of Pb on the nervous system. The method used, namely bibliometric analysis with the help of Publish or Perish (POP) with the keyword Pb on autism and VOS Viewer software and Scopus database. Keyword analysis was conducted on 131 documents from 2013-2024. The results concluded that there are 4 keywords, namely child, lead, effect, and metal and have a great opportunity for future research. This analysis also found that the article entitled "Mechanisms of lead and manganese neurotoxicity" was the most cited article, with 153 citations.